Research on the Sustainable Development Path of China-Belarus New Energy Vehicle Trade from the Perspective of Digital Supply Chain CollaboratioN - Sun, Ke; Jin, Yan (International Journal of Multidisciplinary Research, 2025)
The emergence of the Belt and Road Initiative and sustainable development is the background under which China-Belarus new energy vehicle trade has come to the fore as a new highlight in the realm of cooperation. Based on digital supply chain collaboration, this study uses a comprehensive approach-literature analysis, case studies, and empirical methods-to develop a collaborative model and propose policy recommendations. It also presents the results showing that digital collaboration can improve trade efficiency, reduce carbon emissions, and offer institutional safeguards to China-Belarus green cooperation. This study provides new insights into the integration of new energy vehicle trade and digital supply chains, hence serving as an important reference for fostering sustainable trade across the China-Eurasia region.